The Influence Of Communication, Motivation, And Work Environment On Employee Performance At The DPRD Secretariat Office Empat Lawang - Arusdi, Arusdi; Irwanto, Tito; Astuty, Kamelia (Utami Publisher, 2026)
The purpose of this study was to determine whether communication, motivation, and the work environment influence employees at the Empat Lawang Regional People's Representative Council Secretariat Office. This research is a quantitative descriptive study. Data collection methods used observation and questionnaires, with a sample of 70 respondents. The results showed a multiple linear regression analysis (Y = 55.575 + 0.298 X1 + 0.190 X2 + 0.83 X3 + 2.079). The coefficient is positive, indicating a positive or unidirectional relationship between the communication (X1), motivation (X2), and work environment (X3) variables and employee performance at the Empat Lawang Regional People's Representative Council Secretariat Office. The results show that the communication test (XI) shows t count 3.795 > t table 1.667 and significance 0.001 < 0.05, meaning that communication (XI) has a positive and significant effect on employees at the Empat Lawang DPRD Secretariat Office. The results of the motivation test (X2) show t count 1.729 > t table 1.667 and significance 0.002 < 0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning that motivation (X2) has a positive and significant effect on the performance of employees at the Empat Lawang DPRD Secretariat Office. The results of the work environment (XI) test showed a t-test of 2.589 > t-table of 1.667 and a significance level of 0.006 < 0.05. Therefore, the hypothesis Ha is accepted and Ho is rejected. This means that the environment (XI) has a positive and significant effect on employee performance at the Empat Lawang Regional People's Representative Council Secretariat Office. The F-test value is greater than the F-table value, which is 6.595 > 2.74. This concludes that the hypothesis is accepted. This means that there is a simultaneous influence between communication (XI), motivation (X2), and the work environment (X3) on employee performance (Y) at the Empat Lawang Regional People's Representative Council Secretariat Office. This is evident at a significance level of 0.001 < 0.05.